Detection and Delineation of Oral Cancer With a PARP1-Targeted Optical Imaging Agent. (29th August 2017) - Kossatz, Susanne; Weber, Wolfgang; Reiner, Thomas
More sensitive and specific methods for early detection are imperative to improve survival rates in oral cancer. However, oral cancer detection is still largely based on visual examination and histopathology of biopsy material, offering no molecular selectivity or spatial resolution. Intuitively, the addition of optical contrast could improve oral cancer detection and delineation, but so far no molecularly targeted approach has been translated. Our fluorescently labeled small-molecule inhibitor PARPi-FL binds to the DNA repair enzyme poly(ADP-ribose)polymerase 1 (PARP1) and is a potential diagnostic aid for oral cancer delineation. Based on our preclinical work, a clinical phase I/II trial opened in March 2017 to evaluate PARPi-FL as a contrast agent for oral cancer imaging. In this commentary, we discuss why we chose PARP1 as a biomarker for tumor detection and which particular characteristics make PARPi-FL an excellent candidate to image PARP1 in optically guided applications. We also comment on the potential benefits of our molecularly targeted PARPi-FL-guided imaging approach in comparison to existing oral cancer screening adjuncts and mention the adaptability of PARPi-FL imaging to other environments and tumor types.